Polycomb-mediated transgenerational epigenetic inheritance of Drosophila eye colour is independent of small RNAs - Maximilian Fitz-James; Poppy Sparrow; Christopher Paton; Peter Sarkies (Open Biology)
Transgenerational epigenetic inheritance (TEI) describes the process whereby distinct epigenetic states are transmitted between generations, resulting in heritable gene expression and phenotypic differences that are independent of DNA sequence variation. Chromatin modifications have been demonstrated to be important in TEI; however, the extent to which they require other signals to establish and maintain epigenetic states is still unclear. Here we investigate whether small non-coding RNAs contribute to different epigenetic states of the Fab2L transgene in Drosophila triggered by transient long-range chromosomal contacts, which requires Polycomb complex activity to deposit the H3K27me3 modification for long-term TEI. By analysing mutants deficient in small non-coding RNAs, high-throughput sequencing data, long-range chromosomal contacts and gene expression, we demonstrate that small non-coding RNAs do not contribute directly to initiation or maintenance of silencing. However, we uncover an indirect role for microRNA expression in transgene silencing through effects on the Polycomb group gene Pleiohomeotic. Additionally, we show that a commonly used marker gene, Stubble (Sb), affects Pleiohomeotic expression, which may be important in interpreting experiments assaying Polycomb function in Drosophila development. By ruling out a plausible candidate for TEI at the Fab2L transgene, our work highlights the variability in different modes of TEI across species.